Study on the side friction resistance capacity of prefabricated pipe piles in coral reef strata - Zhang, Hong; Gao, Ran; Luo, Huiwu; Chen, Peishuai; Liu, Haifeng (Frontiers in Earth Science, 2025)
Coral reefs are widely distributed along the “Maritime Silk Road”, and their unique mechanical properties pose numerous challenges for marine engineering construction. The side friction resistance (SFR) capacity of traditional driven piles in coral reef strata remains unclear, and there is a lack of effective calculation methods. Furthermore, the complex marine environment imposes higher requirements on pile foundation construction and durability. In this study, a series of interfacial shear tests were carried out for coral sand and coral reef limestone (CRL) in the sea area near the Maldives islands and reefs, and the distribution law of the SFR of prefabricated pipe piles in coral sand was investigated by using a large-scale pile foundation model test apparatus. The interfacial shear behavior of the coral sand is similar to that of the crushed coral reef limestone, both of which experience ideal elastic-plastic changes, with an interfacial friction angle of approximately 35°. The ultimate SFR of the prefabricated pipe piles in coral sand increases gradually and then plateaus, and the distribution of the SFR along the depth direction can be simplified as a combination of triangular and rectangular patterns. Based on the distribution law of the pile SFR, this study establishes a modified formula for calculating SFR of the pile in coral sand, which is verified by comparing the calculated SFR capacity of driven piles of the China-Maldives Friendship Bridge with the results of the field test piles. This study provides an important theoretical basis and practical guidance for the design and construction of pile foundation engineering in coral reef sea areas such as Maldives.